Investigating the Relationship Between the Expression Level of Mucin Gene Cluster (MUC2, MUC5A, and MUC5B) and Clinicopathological Characterization of Colorectal Cancer: - Hashemi, Mehrdad; Iranmanesh, Hossein; Majd, Ahmad; Nazemalhosseini Mojarad, Ehsan; Zali, Mohammad Reza (Galen Medical Journal, 2021)
Background: Colorectal cancer (CRC) is one of the most common cancers in the world and has a high mortality rate. It is accepted that dysfunction in the expression of mucins are associated with the occurrence and development of CRC. Therefore, the present study aimed to investigate the expression of MUC2, MUC5A, and MUC5B genes in CRC and their relationship with clinicopathological variables. Materials and Methods: The population included 28 patients after a colonoscopy and confirmation of the results. Tumors and parallel adjacent normal tissues from CRC patients were collected. RNA extraction and cDNA synthesis were performed using the corresponding kits. The gene primer was designed and RT-PCR was used to evaluate gene expression. The t-test and ANOVA were used to examine the differences between the different groups. Data analysis was performed using Prism8 software. Tumors from CRC patients were retrospectively collected from Taleghani Hospital, Shahid Beheshti University of Medical Sciences, Tehran, Iran. Results: The results showed that the expression of MUC2, MUC5A, and MUC5B genes was lower in patients with CRC aged 50 years or younger than was in older patients (P<0.05). Only the MUC5B gene expression was associated with tumor grades, which was higher in poorly differentiated tumors. The expression of MUC5A and MUC2 genes was higher in stage IV of the tumor than in other stages (P<0.05). Conclusion: Among the changes in the expression of MUC secretory genes, including MUC2, MUC5A, and MUC5B and clinicopathological variables, there was a relationship that could have prognostic and diagnostic value in CRC. [GMJ.2021;10:e2030]